Changes in pedogenic processes during Pryluky times (Late Pleistocene) in the central part of the Volyn Upland - Bonchkovskyi O.S. (Днепропетровский национальный университет им. Олеся Гончара, 2019)
In the central part of the Volyn Upland, the Pryluky palaeosol unit have been studied in nine loess-soil sites (Boremel 1 3, Novyi Tik, Smykiv, Shybyn, Kolodezhi, Kovban, Novostav). Several sections were excavated along a slope in each studied site in order to reveal the palaeocatena and to study the most complete palaosol successions. The last were found in palaeorelief depressions, which were acting as sediment traps. The genetic interpretation of palaeosols was carried out on the basis on field macromorphological and analytical (micromorphology, grain-size analysis, content of humus and CaCO3) studies. In order to reconstruct the main features of palaeovegetation as an important factor of pedogenesis, pollen analysis of the palaeosols was carried out. It proved a good correspondence between a character of palaeovegetation and a palaeosol type. It has been shown that grain-size composition of the lower Prylyky soils strongly depends on that of parent rocks (Tyasmyn unit of hillwash sandy loam and Kaydaky unit of pedosediment).. The Chernozem-like polygenic soil is the most common within studied area. The lower part of soil has signs of podsolization (powder of SiO2, light color, low content of clay). The upper Pryluky soils are distorted by erosional and cryogenic processes (mainly by solifluction textures) that hampers the interpretation of diagenetic and original pedogenic processes. The abundant bioturbations in the subsoil (the largest number among the Late Plestocene soils), high content of humus, complex microaggregates, but leach in the СaCO3 have been established to Pryluky soil unit. The presence of relic pedogenic signs in the polygenetic soil, an assumption is made about the existence of several stages of its formation. The investigation of pedocomplexes confirm it. The study of well-developed pedocomplexes in sedimentation traps allows the allocation of those pedogenic phases during Pryluky times: pl1b1 – Podzolic, Cryptopodzolic, Albeluvisol, Albic Luvisol; pl1b2 – Luvic Chernozem, Chernic Chernozem and Cryptopodzolic,; pl1с – Umbrisol and Cambic Luvisol; pl3a – Luvic Cambisol; pl3b1 – Luvisol and Luvic Cambisol; pl3b2 – Mollic and Luvic Cambisol.
Keywords: pedocomplex; pedogenetic phases; micromorphological features; pedosediment; palaeosol catena; ґрунтова світа; стадія та фаза педогенезу; мікроморфологічна будова; педоседимент; ґрунтова катена